2019
DOI: 10.1097/scs.0000000000005227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bupivacaine Versus Bupivacaine Plus Dexamethasone-Soaked Nasal Packing After Endoscopic Nasal Surgery

Abstract: Background: The aim of this randomized prospective study was to investigate the postoperative analgesic effectiveness of bupivacaine versus bupivacaine plus dexamethasone-soaked nasal packing in patients scheduled for endoscopic nasal surgery. Methods: Sixty American Society of Anesthesiologists groups I and II patients aged 18 to 65 years and scheduled for endoscopic nasal surgery were assigned into 2 groups. Group B received 8 mL 0.5% bupivacaine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results showed that the intensity of pain in the experimental group (dexamethasone) was lower than in the control group at 12 and 24 hours after surgery, indicating that dexamethasone was able to significantly reduce pain in patients. These findings are consistent with the results of studies by Pehora et al ( 7 ), Yayik et al ( 10 ), Badran et al ( 11 ), and Kim et al ( 12 ). For instance, Badran et al demonstrated that adding 8 mg of perineural dexamethasone to 30 cc of bupivacaine 0.5% improved postoperative pain relief in shoulder surgery without apparent side effects and prolonged the duration of the block ( 11 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that the intensity of pain in the experimental group (dexamethasone) was lower than in the control group at 12 and 24 hours after surgery, indicating that dexamethasone was able to significantly reduce pain in patients. These findings are consistent with the results of studies by Pehora et al ( 7 ), Yayik et al ( 10 ), Badran et al ( 11 ), and Kim et al ( 12 ). For instance, Badran et al demonstrated that adding 8 mg of perineural dexamethasone to 30 cc of bupivacaine 0.5% improved postoperative pain relief in shoulder surgery without apparent side effects and prolonged the duration of the block ( 11 ).…”
Section: Discussionsupporting
confidence: 93%
“…The addition of lidocaine to Nasopore ® , intra‐operatively and 8 hours post‐surgery appeared to be significantly reduced immediate post‐operative pain for up to 16 hours after surgery, 1887 while gloved Merocel ® packs were found to cause less discomfort on removal than standard Merocel ® packs 2178 . In an RCT Yayik et al showed that adding bupivacaine and dexamethasone to the nasal pack decreased pain and analgesic requirements in the first 24 hours after surgery 2199 . In another RCT Garzaro et al showed that adding 5 mL of lidocaine to a PVA sponge did not result in less pain then a saline soaked sponge in a gloved finger 2200 .…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…4 Many pharmacological or non-pharmacological methods have been attempted for pain management after septorhinoplasties such as nonsteroidal anti-inflammatory analgesics, intravenous (IV) lidocaine infusion, a-2 receptor agonists, gabapentinoids, and intraoperative local anesthetic infiltration. [5][6][7] In the last 2 decades, many studies have been conducted on the effects of ketamine on postoperative pain, chronic pain, depression, and postop delirium treatment. [8][9][10][11] Ketamine is a phencyclidine derivative synthesized in 1962.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many pharmacological or non-pharmacological methods have been attempted for pain management after septorhinoplasties such as nonsteroidal anti-inflammatory analgesics, intravenous (IV) lidocaine infusion, α-2 receptor agonists, gabapentinoids, and intraoperative local anesthetic infiltration. 5 -7…”
Section: Introductionmentioning
confidence: 99%